Sexual Harassment as an Emerging Problem in Peruvian University Contexts - Atoche-Silva , Luz Angelica; Remaycuna-Vasquez, Alberto; Carrión-Barco, Gilberto; Padilla-Caballero, Jesús Emilio Agustín; Pantoja-Tirado, Lucia Ruth; Calonge De la Piedra, Dina Marisol (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
Considering the prevalence of sexual harassment, especially in university contexts, it is essential to have a validated instrument to identify these characteristics in the educational community. For this reason, this study aimed to analyze the psychometric processes of the sexual harassment scale on university campuses. Using an instrumental design and a sample of 927 students, it was found that the values of the evidence of construct validity and reliability are acceptable. The practical implications of validating the instrument that will allow the identification of sexual harassment problems to promote symmetrical coexistence between men and women are highlighted.